2017
DOI: 10.1177/1748895817739664
|View full text |Cite
|
Sign up to set email alerts
|

Empowering the police to fight terrorism in Israel

Abstract: Police agencies are often seen as reliant on the public to give them the authority and power necessary to carry out their responsibilities, including controlling crime. As many police agencies begin to take on counterterrorism functions, this empowerment of the police is necessary in their fight against terrorism. To our knowledge, no study to date has focused on the empowerment of the police in their counterterrorism role and the factors that influence the willingness of the public to afford the police discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…First, perceptions of legitimacy matter for public willingness to empower police. Consistent with findings by Sunshine and Tyler (), Pryce (), and Metcalfe and Hodge (), as citizen perceptions of police legitimacy increase, so too does their willingness to empower the police. This finding builds on prior empowerment research in two important ways.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…First, perceptions of legitimacy matter for public willingness to empower police. Consistent with findings by Sunshine and Tyler (), Pryce (), and Metcalfe and Hodge (), as citizen perceptions of police legitimacy increase, so too does their willingness to empower the police. This finding builds on prior empowerment research in two important ways.…”
Section: Discussionsupporting
confidence: 81%
“…11 To the extent that other countries are experiencing militarization, or already maintain a militarized police force (Beede 2008;Lutterbeck 2004;McCulloch 2004), questions about empowerment persist and should be examined. We are aware of only one study examining public empowerment of police in a non-American context (see Metcalfe and Hodge 2017). In non-Western or developing countries, where police effectiveness, rather than procedural justice, appears to drive legitimacy (Tankebe 2009(Tankebe , 2013, perceived effectiveness may be more salient for public willingness to continue empowering police (Pryce 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has demonstrated the breadth of the legitimacy–empowerment link. Among Israelis, Metcalfe and Hodge (2018) found trust in police and perceived obligation to obey independently increased support for allowing the police to fight terrorism. Yesberg and Bradford (2018) found that London residents who more strongly trusted the police were more supportive of arming the police.…”
Section: Legitimacy and Public Empowerment Of Policementioning
confidence: 99%
“…Other work has put institutional trust centre-stage. For example, in a study of police-citizen relations in Israel, Metcalfe et al(2017) argued that:…”
Section: Police Legitimacy: International Perspectivesmentioning
confidence: 99%